2018
DOI: 10.14740/jh449w
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Chromic Status of Red Blood Cells Are Significantly Influenced by Gestational Diabetes

Abstract: Background: The study shows the effect of hyperglycemia on RBCs in terms of morphological changes and their chromic status in women with gestational diabetes mellitus (GDM). Methods: A total of 100 pregnant women were enrolled from Maternity and Children Hospital, Qassim, Saudi Arabia including 40 women with confirmed GDM (group-1), 30 women with either type 1 or type 2 diabetes (group-2) and 30 women with normal pregnancy without GDM or pre-gestational diabetes (control group-3). Demographic, anthropometric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…[26] Anisocytosis was reported to be more prevalent in GDM. [27] In their cohort study including 16971 adults Wang et al found that each unit increase of RDW was associated with a 16% higher incident diabetes and concluded that high RDW was associated with high risk of diabetes. [25] The number of studies assessing the association between RDW and GDM is scarce and there are conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Anisocytosis was reported to be more prevalent in GDM. [27] In their cohort study including 16971 adults Wang et al found that each unit increase of RDW was associated with a 16% higher incident diabetes and concluded that high RDW was associated with high risk of diabetes. [25] The number of studies assessing the association between RDW and GDM is scarce and there are conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it is evident that HG conditions have detrimental effects on different cell types, including cancer cells, and may also change their normal functions, i.e. migration potential and invasiveness[ 1 , 2 , 48 - 50 ]. Hence, understanding the mechanism of apoptosis by chronic exposure to HG, both in vitro and in vivo , will help efforts to combine preconditioning strategies, especially the subcellular preconditioning approach.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that when the coefficient of variation of RDW was greater than 13.6, the likelihood of lung tissue injury increased by 9.3 times, and it was a lung volume marker for COVID-19 severity. 35 Studies have proved that increased RDW is common in human disorders, including cardiovascular disease, 36 venous thromboembolism, 37 cancer, 38 diabetes, 39 community-acquired pneumonia, chronic obstructive pulmonary disease, 37 liver, 40 and kidney failure, 41 and so on. Increased RDW reflects a severe dysregulation of erythrocyte homeostasis, including impaired erythropoiesis and abnormal erythrocyte survival.…”
Section: Discussionmentioning
confidence: 99%